Ricebean A nutritious and resilient crop under present scenario - Tripathi, Kuldeep; Gore, Padmavati G. (Indian Farming, 2018)
Ricebean is a multi-functional crop. It is mainly used for human dietary uptake as the dried grains are rich in protein, minerals and vitamins and also used for fodder. Nitrogenfixing ability makes ricebean important for green manuring. Besides this, it is a very hardy crop, possesses many useful genes which provide resistance to biotic and abiotic stress. These characteristics of ricebean are very important to tackle the problem of changing climate. Considering its role in food and nutritional security, utilization of ricebean genetic resources is essential in present scenario to make it as food legume of 21st century.